Dampak Privasi, Keamanan, Kepercayaan, dan Pengalaman terhadap Niat Mahasiswa Akuntansi untuk Bertransaksi di E-Commerce - Andi Nursyamsi Amin (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of privacy, security, trust and experience on the intentions of Accounting students to transact in e-commerce. The population in this study were students majoring in Accounting who had taken or were taking Information Systems courses at several campuses in the city of Makassar at random. The sample used was 100 accounting students and users of e-commerce applications. The results of this study partially show that the influence of privacy and security and trust has no effect, while experience has a positive and significant effect on the intention to transact in e-commerce in Accounting Students. The results of the research simultaneously show that the variables of Privacy, Security, Trust and Experience simultaneously affect the intention of students to transact in e-commerce.